CURRENT STATUS OF LDL-CHOLESTEROL CONTROL AT DISCHARGE IN PATIENTS WITH CEREBRAL INFARCTION AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe LDL-C levels and the proportion of patients with ischemic stroke achieving an LDL-C level of
Keywords: ischemic stroke; LDL-C; lipid control; secondary prevention; cardiovascular risk.